2011
DOI: 10.1111/j.1476-5381.2011.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial pharmacokinetics of ebastine, a substrate for cytochrome P450 2J, in rat isolated heart

Abstract: BACKGROUND AND PURPOSEIt is well established that cytochrome P450 2J (CYP2J) enzymes are expressed preferentially in the heart, and that ebastine is a substrate for CYP2J, but it is not known whether ebastine is metabolized in myocardium. Therefore, we investigated its pharmacokinetics in the rat isolated perfused heart. EXPERIMENTAL APPROACHRat isolated hearts were perfused in the recirculating mode with ebastine for 130 min. The concentrations of ebastine and its metabolites, hydroxyebastine and carebastine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Therefore, we first measured NADPH oxidation by CYP2J2‐CPR‐ND in presence of ebastine. CYP2J2 is mainly responsible for the hydroxylation of the H1‐receptor antagonist ebastine in human liver and intestinal microsomes . We observed that NADPH oxidation was the greatest in 20% POPS discs, followed closely by 40% POPS discs [Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, we first measured NADPH oxidation by CYP2J2‐CPR‐ND in presence of ebastine. CYP2J2 is mainly responsible for the hydroxylation of the H1‐receptor antagonist ebastine in human liver and intestinal microsomes . We observed that NADPH oxidation was the greatest in 20% POPS discs, followed closely by 40% POPS discs [Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, in isolated rat heart hydroxylation of the H 1 receptor antagonist, ebastine to hydroxyebastine and carebastine was detected and compared with human liver microsomes and showed a similar metabolism profile; however, as there was no comparison with metabolism in the human heart, it is difficult to ascertain comparative activity between CYP2J2 CYP2J2 and Cardiotoxicity and CYP2J3. It is also unclear whether other P450 enzymes could be responsible, in part, for ebastine metabolism (Kang et al, 2011). Overall, the metabolic activity of CYP2J2 in the liver and its ability to metabolize a wide array of drugs, coupled with its high expression in the heart, warrant further studies to clarify the significance of cardiac CYP2J2 in drug metabolism in physiologic relevant systems.…”
Section: Humanmentioning
confidence: 99%